ANALISIS KEMAMPUAN TEKNIK DASAR BOLA VOLI PADA ATLET KLUB GUNTUR 1000 KOTA PADANG: Analysis of Basic Volleyball Technique Skills in Athletes of Guntur 1000 Volleyball Club, Padang City - AL RIPSI, FIQIH; Rifki, Muhammad Sazeli; Mukhtarsyaf, Fahd; Nelson, Sonya (Jurnal IKEOR, 2026)
Basic technical skills are an important factor in determining the performance of volleyball athletes. However, based on observations at the Guntur 1000 Volleyball Club in Padang City, athletes’ basic technical skills are still not optimal, as indicated by errors in serving, passing, and smashing. This study aims to analyze the basic volleyball technical skills of athletes at the Guntur 1000 Volleyball Club, Padang City. This study employed a descriptive quantitative method using tests and measurements. The population consisted of all athletes registered in the Guntur 1000 Volleyball Club, totaling 65 athletes. The sample included 33 athletes who actively participated in training sessions. The instruments used were the AAHPER Serving Accuracy Test, Brumbach Forearm Pass Wall-Volley Test, AAHPER Face Pass Wall-Volley Test, and the Spike Test. The results showed that: (1) serving ability was in the sufficient category, (2) forearm passing ability was in the sufficient category, (3) overhead passing ability was in the sufficient category, and (4) smash ability was in the poor category.